IMPACT OF TH17/TREGFOXP3 CELLS RATIO ON RHEUMATOID ARTHRITIS PATIENTS RECEIVING ANTI TNF- THERAPY-. - MOHSEN, ENAS RIYADH; ALI, NAAEL H. (Journal of Duhok University, 2021)
In order to determine the correlation between disease activity of RA with the Th17/TregFoxp3 cells ratio in patients undertherapy with Anti-TNF-alpha which is the aim of present study, Ninety-seven patients with RA and healthy control groups were included in this case control study, eighty-four patients divided into four groups; 25 patients receiving only MTX; 18 patients receiving monotherapy (anti- TNF); 26 patients receiving combined therapy (MTX + anti-TNF); 15 patients with RA not receiving any drug (positive control). Other thirteen healthy people considered as negative control were enrolled in this study. Patients with RA were attending Basrah General Hospital, Rheumatology Unite, Biological Therapy Center for receiving anti-TNF therapy. Flowcytometry was used for measuring TregFoxp3 and Th17 markers and DAS-28 score was used for measuring RA disease activity. Anti TNF inhibitors (Infliximab and Etanercept) were measured as well. Other inflammatory and hematological parameters were also measured (ESR, total WBC, Lymphocytes, monocytes and neutrophil counts). Resulted, DAS-28 as disease activity score was significantly correlated with Th17/ TregFoxp3 ratio and with the TH17 cells count. Statistically, Th17/ TregFoxp3 ration was not correlated with BMI, morning stiffness, and duration of the disease. In a Conclusion, Th17/Treg Foxp3 ratio correlated significantly with DAS-28 as RA disease activity. The lower Tregs Foxp3 frequency, the higher the DAS score reflecting higher disease activity. In combined therapy group, disease activity was found lower than other patient groups indicating for the effect of this combination between MTX and anti-TNF. Herein, we demonstrated that the main advantage of this combined therapy in RA patients was the reversion of Th17 cell expansion